STUDY OF SUITABILITY AND ZONATION OF LAMPUNG BAY WATERS TOWARDS PHYSICAL CARRYING CAPACITY OF THE AREA FOR GROUPER CULTIVATION IN FLOATING NET CAGES (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
In 1990, grouper cultivation using floating net cages (KJA) was developed to meet market demand. This study aimed to assess the suitability and zoning of water towards the physical carrying capacity of the Lampung bay area for grouper cultivation in floating net cages (KJA). The suitability assessment was based on physical, chemical, and socio-economic aspects. The physical carrying capacity of the area was analyzed from the results of the suitability criteria. The area that met the suitability criteria of Lampung bay were high (67.64 ha), medium (5,838.17 ha), low (3,214.89 ha), and not suitable (35.95 ha). The next step is overlaying with zoning; it has a result that a decrease of the area of ​​high suitability to (1,446. 28 ha), medium (23.71 ha), and low (440.05) ha and not suitable area increased to (7,226.62 ha). The physical carrying capacity of the Teluk Lampung area is 13,450 KJA units or with a production potential of 24,754 tons. With a decrease in the suitable area, the physical carrying capacity will decrease to 4,545 units of KJA or a production potential of 8,365 tons. The results of this study indicate that the overlay with the zoning plan reduces the area suitable for KJA cultivation activities which in turn causes a decrease in the physical carrying capacity of the area.